Early Program Assessment of the Haryana Wheat Flour Fortification Program, India. (14th June 2022) - Duggal, Mona; Rosenthal, Jorge; Kaur, Manmeet; Singh, Neha; Das, Reena; Shandil, Nupur; Khullar, Sonia; Dalpath, Suresh; Mehta, Rajesh; Deo, Pushpa; Gupta, Rachita; Raina, Neena; et al.
Abstract: Objectives: In 2018, a wheat flour fortification program with iron, folic acid, and vitamin B12 fortificants was established within the government-run Public Distribution System (PDS) in Ambala District, Haryana, India to address micronutrient deficiencies. PDS provides basic food and non-food commodities to the families below poverty level at subsidised prices. This study aims to assess household fortified wheat flour consumption among PDS recipients. Methods: In 2021, we conducted a household survey and interviewed women aged 18–49 years (WRA) about consumption of wheat flour. A systematic probability sample design was used to select 358 households with WRA from a listing of all household beneficiaries enrolled in PDS who were living in the Naraingarh and Barara communities in Ambala District where the wheat flour fortification program was implemented. We assessed the percentages of households who have received and consumed fortified wheat flour from PDS, and assessed the perceived quality of fortified wheat flour compared to non-fortified wheat flour from other sources. Results: We were able to reach 88% of the selected households (314/358) and 291 WRA agreed to participate (response rate 93%). Almost 99% (288/291) of households were eligible to obtain fortified wheat flour through PDS and among those eligible, 285 (99%) obtained fortified wheat flour monthly. Household consumption of fortified wheat flour was 98%, and 71% consumed all the fortified wheat flour supply before consuming other non-fortified wheat flours. Among households that reported consumption of fortified wheat flour, 63% reported quality of the fortified wheat flour was similar or better than non-fortified wheat flour from other sources. Conclusions: Receipt and consumption of fortified wheat flour among PDS beneficiaries was very high. A majority of households reported consumption of fortified wheat flour first before other non-fortified wheat flour and that the quality of fortified wheat flour was similar or better than other non-fortified wheat flour. Periodic assessment of the wheat flour fortification program would be helpful to ensure continual high consumption of fortified wheat flour by PDS beneficiaries. Funding Sources: U.S. Centers for Disease Control and Prevention provided funding for the assessment.